2021
DOI: 10.1038/s41598-021-01990-0
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop wearable naloxone injector system

Abstract: Overdoses from non-medical use of opioids can lead to hypoxemic/hypercarbic respiratory failure, cardiac arrest, and death when left untreated. Opioid toxicity is readily reversed with naloxone, a competitive antagonist that can restore respiration. However, there remains a critical need for technologies to administer naloxone in the event of unwitnessed overdose events. We report a closed-loop wearable injector system that measures respiration and apneic motion associated with an opioid overdose event using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…We classified technologies into 3 main groups according to their main function, namely, “OD alert,” “OD response,” and “combined OD alert and response.” These are shown in Tables 1 - 3 . Multimedia Appendix 2 [ 24 - 38 , 40 - 47 ] displays more detailed information about each study (ie, intervention, function, focus, device, theme, and study design). Although there is frequently a degree of overlap between the first 2 groups, as all devices ultimately need to combine OD alert and response, this classification is based on the main focus of the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We classified technologies into 3 main groups according to their main function, namely, “OD alert,” “OD response,” and “combined OD alert and response.” These are shown in Tables 1 - 3 . Multimedia Appendix 2 [ 24 - 38 , 40 - 47 ] displays more detailed information about each study (ie, intervention, function, focus, device, theme, and study design). Although there is frequently a degree of overlap between the first 2 groups, as all devices ultimately need to combine OD alert and response, this classification is based on the main focus of the study.…”
Section: Resultsmentioning
confidence: 99%
“…There are some devices being developed that attempt to cover both functions by acting as a closed-loop system. In this case, the device uses a sensor that, if detecting an OD, sends a signal to an automatic antidote dispenser attached to the body in the form of either an injection [ 24 , 39 , 45 , 48 , 49 ] or an implant [ 25 ]. At present, the studies we identified are in the prototype phase and are more focused on the antidote dispenser than on the sensor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other approaches have described the use of digital health tools to facilitate harm reduction, including opioid overdose detection and automatic delivery of the antidote naloxone (13,14). For example, Chan et al evaluated the computational and mechanical functionality of a novel closed-loop, on-body sensor designed to automatically inject naloxone after detecting an opioid overdose (15).…”
Section: Introductionmentioning
confidence: 99%